UPAYA MENINGKATKAN PRESTASI BELAJAR AKUNTANSI BIAYA DENGAN MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALITY (TAI) - Alfiana Fitri (Jurnal Ekonomi dan Manajemen, 2016)
This research aims to implement cooperative learning methods based Team Assisted Individuality (TAI) to enhance the ability of management students in the preparation of Cost Of Good Sold Report. This study design is a class action research (PTK) Experiments with one cycles. The subjects were students of S1Management Universitas Internasional Semen Indonesia. This research used observation, documentation, field notes, and test for data collection technique. Data were analyzed using descriptive quantitative analysis and test different. The results showed that the application of cooperative learning methods based Team Assisted Individuality (TAI) can improve the ability of management students in the preparation of Cost Of Good Sold Report.